Exosomal miR-130b-3p Promotes Progression and Tubular Formation Through Targeting PTEN in Oral Squamous Cell Carcinoma - Yan, Wei; Wang, Yuping; Chen, Yong; Guo, Yanjun; Li, Qiang; Wei, Xiaotong (Frontiers in Cell and Developmental Biology, 2021)
Oral squamous cell carcinoma (OSCC), accounting for two-thirds of head and neck cancer, is characterized by poor prognosis and a high rate of mortality. Exosomes have emerged as potential molecule-shuttle in intercellular communication, thereby regulating the physiological processes of recipient cells. To date, the effect of exosomal microRNAs (miRNAs) on the progression of OSCC has not been fully investigated. In this study, we found that the protein, but not mRNA expression of Phosphatase and tensin homolog deleted on chromosome 10 (PTEN) was decreased in OSCC. The results revealed that miR-130b-3p was an important negative regulator for PTEN expression. Additionally, overexpression and knockdown of miR-130b-3p enhanced and inhibited angiogenesis in human umbilical vein endothelial cells (HUVECs), respectively. Also, miR-130b-3p was transferred by exosomes to HUVECs and then promoted angiogenesis and inhibit the expression of PTEN. Furthermore, exosomal miR-130b-3p derived from OSCC cells promoted tumor growth and blood vessel formation in the xenograft mice model. Taken together, we demonstrated that exosome-mediated miR-130b-3p promoted progression and tubular formation in OSCC in vitro and in vivo. These results would provide new insight into exploring biomarkers and effective therapeutic strategies for OSCC.